EMAS position statement: Vitamin D and menopausal health. (March 2023) - Anagnostis, Panagiotis; Livadas, Sarantis; Goulis, Dimitrios G.; Bretz, Silvia; Ceausu, Iuliana; Durmusoglu, Fatih; Erkkola, Risto; Fistonic, Ivan; Gambacciani, Marco; Geukes, Marije; Hamoda, Haitham; Hartley, Caoimhe; et al.
Highlights: Vitamin D deficiency compromises musculoskeletal health and may be associated with postmenopausal symptoms. Vitamin D deficiency is associated with an increased prevalence of both cardiovascular disease and several types of cancer, as well as an increased risk of acute respiratory infections and autoimmune diseases. Vitamin D supplementation, when co-administered with calcium, may reduce the risk of fracture. Vitamin D supplementation is not recommended for postmenopausal symptom relief or risk reduction for cardiovascular disease and cancer. Abstract: Introduction: There is increasing evidence that vitamin D has widespread tissue effects. In addition to osteoporosis, vitamin D deficiency has been associated with cardiovascular disease, diabetes, cancer, infections and neurodegenerative disease. However, the effect of vitamin D supplementation on non-skeletal outcomes requires clarification, especially in postmenopausal women. Aim: This position statement provides an evidence-based overview of the role of vitamin D in the health of postmenopausal women based on observational and interventional studies. Materials and methods: Literature review and consensus of expert opinion. Results and conclusions: Vitamin D status is determined by measuring serum 25-hydroxyvitamin D levels. Concentrations <20 ng/ml (<50 nmol/l) and <10 ng/ml (<25 nmol/l) are considered to constitute vitamin D deficiency and severe deficiency, respectively. Observational data suggest an association between vitamin D deficiency and adverse health outcomes in postmenopausal women, although they cannot establish causality. The evidence from randomized controlled trials concerning vitamin D supplementation is not robust, since many studies did not consider whether people were deficient at baseline. Moreover, high heterogeneity exists in terms of the population studied, vitamin D dosage, calcium co-administration and duration of intervention. Concerning skeletal health, vitamin D deficiency is associated with low bone mass and an increased risk of fractures. Vitamin D supplementation at maintenance doses of 800–2000 IU/day (20–50 μg/day), after repletion of vitamin D status with higher weekly or daily doses, may be of benefit only when co-administered with calcium (1000–1200 mg/day), especially in the elderly populations and those with severe vitamin D deficiency. Concerning cardiovascular disease, vitamin D deficiency is associated with an increased prevalence of cardiovascular risk factors, mainly metabolic syndrome, type 2 diabetes mellitus and dyslipidemia. Vitamin D deficiency, especially its severe form, is associated with an increased risk of cardiovascular events (coronary heart disease, stroke, mortality), independently of traditional risk factors. Vitamin D supplementation may have a modestly beneficial effect on lipid profile and glucose homeostasis, especially in obese individuals or those ≥60 years old and at doses of ≥2000 IU/day (≥50 μg/day). However, it has no effect on the incidence of cardiovascular events. Concerning cancer, vitamin D deficiency is associated with increased incidence of and mortality from several types of cancer, such as colorectal, lung and breast cancer. However, the data on other types of gynecological cancer are inconsistent. Vitamin D supplementation has no effect on cancer incidence, although a modest reduction in cancer-related mortality has been observed. Concerning infections, vitamin D deficiency has been associated with acute respiratory tract infections, including coronavirus disease 2019 (COVID-19). Vitamin D supplementation may decrease the risk of acute respiratory tract infections and the severity of COVID-19 (not the risk of infection). Concerning menopausal symptomatology, vitamin D deficiency may have a negative impact on some aspects, such as sleep disturbances, depression, sexual function and joint pains. However, vitamin D supplementation has no effect on these, except for vulvovaginal atrophy, at relatively high doses, i.e., 40, 000–60, 000 IU/week (1000–1500 IU/week) orally or 1000 IU/day (25 μg/day) as a vaginal suppository.